2020
DOI: 10.1186/s12891-020-3120-0
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of inflammatory mediators in the synovial fluid related to pain in knee osteoarthritis

Abstract: Background: Inflammatory mediators in the synovial fluid (SF) play critical roles in the initiation and development of pain in knee osteoarthritis (KOA). However, data for inflammatory marker expression are conflicting, and the role of SF inflammatory mediators in neuropathic pain is not clear. Therefore, the aim of this study was to identify SF inflammatory mediators associated with nociceptive and neuropathic pain in KOA. Methods: Levels of IL-1β, IL-6, TNF-α, macrophage colony-stimulating factor, MMP-3, MMP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“… 54 Collectively, these actions may help to resolve inflammation and attenuate cartilage degradation, both of which play an important role in the pathology and clinical manifestations of OA. 2 , 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 54 Collectively, these actions may help to resolve inflammation and attenuate cartilage degradation, both of which play an important role in the pathology and clinical manifestations of OA. 2 , 3 …”
Section: Discussionmentioning
confidence: 99%
“…2 This inflammation, coupled with progressive articular erosion, causes pain, progressive loss of function, and diminished quality of life. 3,4 Given its high prevalence, knee OA is a leading cause of physical disability in the aging population. 5 There are currently few effective conservative treatment modalities for symptomatic knee OA, none of which prevent disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation tests have been previously used to assess WOMAC data. 36,37 We used nonparametric correlation tests and determined that lower scores at 3, 6, and 12 months correlated with saline or PRP treatment for pain, stiffness, physical function, and VAS (Table S2). Incidence of significant correlations appeared to be more frequent at 6 months following treatment for both saline and PRP when compared to baseline.…”
Section: Knee Radiographsmentioning
confidence: 99%
“… 7 Therefore, the boundary between inflammatory OA and degenerative OA is becoming unclear as understanding of the ongoing immune processes within a degenerate joint becomes clearer. 8 , 9 In particular, inflammation has been strongly implicated in the pathogenesis of OA. 10 , 11 Previous studies have reported increased levels of pro-inflammatory cytokines, such as tumor necrosis factor (TNF) α, interleukin (IL)-1β, and IL-6 in OA fluid and tissue.…”
Section: Introductionmentioning
confidence: 99%